2017
DOI: 10.1186/s12916-017-0899-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of people with dementia, delirium, and unspecified cognitive impairment in the general hospital: prospective cohort study of 10,014 admissions

Abstract: BackgroundCognitive impairment of various kinds is common in older people admitted to hospital, but previous research has usually focused on single conditions in highly-selected groups and has rarely examined associations with outcomes. This study examined prevalence and outcomes of cognitive impairment in a large unselected cohort of people aged 65+ with an emergency medical admission.MethodsBetween January 1, 2012, and June 30, 2013, admissions to a single general hospital acute medical unit aged 65+ underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
141
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 36 publications
10
141
2
7
Order By: Relevance
“…In most studies, CI or dementia increased length of hospital stay (LOS) . (Table ) Patients with DSD had longer mean LOS than those with dementia or delirium alone . Concurrent dementia extends stays in older patients with hip fracture and haemorrhagic peptic ulcer disease .…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…In most studies, CI or dementia increased length of hospital stay (LOS) . (Table ) Patients with DSD had longer mean LOS than those with dementia or delirium alone . Concurrent dementia extends stays in older patients with hip fracture and haemorrhagic peptic ulcer disease .…”
Section: Resultssupporting
confidence: 55%
“…Moderate and severe CI was associated with mortality after ICU admission, even adjusting for acuity scores (Acute Physiology and Chronic Health Evaluation II . A large cohort demonstrated significant differences in mortality for patients with CI but no diagnosis of dementia as compared to patients with no CI (11.8% vs 9.0%), and a further study showed a difference between “all‐cause” CI and no CI (13.6% vs 9.0%) . The presence of CI, regardless of dementia, may independently predict in‐hospital mortality, with the highest risk in patients with severe CI …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 1 study reported a 72% lower odds for PWD to have a LOS of 10 days or more compared to PwoD (95% CI: 0.1‐0.4) . With exception of 1 study conducted in Ireland, the remaining studies across Europe reported a longer LOS for PWD of up to 22 days . Within countries, the different studies were consistent in reporting a longer LOS for PWD compared to PwoD; however, the difference in the LOS varied up to 13 days …”
Section: Resultsmentioning
confidence: 93%
“…Seventeen studies across 7 countries were conducted in Europe: 3 studies each in Italy, Germany, Ireland, and the UK, 2 studies from Austria and Finland, as well as 1 study from Spain . The difference in LOS among PWD compared to PwoD ranged from 0.4 to 22 days .…”
Section: Resultsmentioning
confidence: 99%